Pengelolaan Stres dan Peningkatan Produktivitas Kerja selama Work From Home pada Masa Pandemi COVID-19 - Muhammad Ishak Shabuur; Wustari L. Mangundjaya (Jurnal Psikologi Udayana, 2020)
When the COVID-19 pandemic spread globally, public health guidelines recommend all workers to work from home (WFH). In Indonesia, not many companies have implemented WFH before because of traditional management practices, of course adjusting to WFH is a new experience for most workers. Meanwhile, most of the studies reviewed regarding the effects of quarantine reported negative psychological effects including symptoms of stress, confusion, and anger. Based on this situation, this study aims to review the influence of work flexibility attitudes towards WFH through flexibility working options on work productivity during the COVID-19 Pandemic quarantine period and test the coping strategy as a moderator on the relationship between the two variables. This study involved 421 working from home employees in the private sector, public sectors and government in Indonesia. Participants were taken using convenience sampling techniques through the distribution of questionnaires online. Testing for moderation effects is done by using moderated regression analysis (MRA) technique. The results show that coping strategy positively moderates the relationship, such that the relationship between flexibility working options and work productivity is increasing when employee implement coping mechanisms that focus on problems for control stressors and maintain their work productivity during the COVID-19 pandemic.